Zgornja gozdna meja v Kamniških Alpah v geografski luči - Lovrenčak, Franc (Geografski zbornik, 1977)
The study discusses the upper timberline in the Kamnik Alps (Slovenia) as one of the most characteristic features of the high mountain landscape. The upper timberline is a belt of varying width whose forest becomes less and less dense with increasing height until it finally disappears. Timberline is the result of a complex interaction of various factors of the mountain world. Thus the study shows the natural conditions characteristic of the Kamnik Alps and Snežnik Mt. and surveys the species of trees which the timberline consists. Furthermore discusses the influence of individual natural factors (landform, climate, soil, and water) upon this timberline in the Kamnik Alps are discussed in detail.
Keywords: fitogeografija; fizična geografija; geografija; geography; gozdna meja; Kamnik Alps; Kamniške Alpe; physical geography; phytogeography; timberline; upper timberline; zgornja gozdna meja